Comparison of proviral load levels and mRNA expression of cytokines in peripheral blood mononuclear cells and milk somatic cells from BLV-infected cattle - Dolcini, Guillermina Laura (2021)
The bovine leukemia virus (BLV) is an exogenous retrovirus belonging to the Deltaretrovirus genus. This enveloped virus naturally infects B-lymphocytes causing enzootic bovine leukemia (EBL), which is spread worldwide, mainly in dairy cattle. The virus might produce cell-mediated immunity disorders, which may lead to opportunistic infections in BLV-infected cattle. Thus, the performance of dairy cattle is impaired, leading to large economic losses in the dairy industry. A study was carried out to investigate the levels of proviral load as well as mRNA expression of cytokines in peripheral blood mononuclear cells (PBMC) and milk somatic cells (SC) of low proviral load (LPL), high proviral load (HPL) and uninfected cattle (controls). A total of 51 BLV- infected cows and 16 controls were included. The levels of proviral loadin PBMC and SC as well as the expression levels of cytokine mRNA between LPL and HPL cattle were measured by real-time PCR (qPCR).